The Effect of Pulmonary Ventilation Exercises and some Respiratory Indicators in the Preparation for Olympic Lift and Achievement for Advanced Lifters - Hayder Jabbar Abd (Institute of Medico-legal Publications Pvt Ltd, 2021)
The research aims to identify the effect of pulmonary ventilation exercises and some respiratory indicatorson the preparation of the Olympic jacks and achievement for the advanced fourths, so the experimentalapproach was adopted to treat the research problem, the research sample was intentionally chosen from (20)different players, they were divided into two experimental and control groups using the method of randomdivision.(1) The homogeneity and equivalence processes were performed to initiate one point for the data ofthe two research samples, after taking pre-measurements for them (height, age, ve. Vs. vo2 max), a trainingapproach was designed to develop pulmonary ventilation and know its effect on other research variables,and the results of the tribal arithmetic media were compared And the dimensionality of the two groups andtreating them statistically, as the most important conclusions were reached which are the void filling wheninhaling and holding the breath with the need to take adequate inhalation at a rate of (RR10) inhalation andexhalation operations before lifting that lead to the best achievement. .(2)